2000
DOI: 10.1159/000014651
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Temperature Signal on Sleep in Mammals

Abstract: The influence of the temperature signal on sleep may be considered physiologically specific if it entails thermoreceptor activation. Experimental evidence shows that sleep time peaks at neutral ambient temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…This would suggest that there is a threshold of temperature beyond which sleep is either drastically reduced or altogether eliminated. This is supported by several studies (e.g., [70][71][72]), which found that alterations of ambient temperature tend to affect the timing and periodicity of sleep, while altering temperature far outside the thermal neutral zone can affect sleep duration as well. A study in bats found that when ambient temperatures exceeded 35 • C, no sleep was observed [73].…”
Section: Lights-offsupporting
confidence: 53%
“…This would suggest that there is a threshold of temperature beyond which sleep is either drastically reduced or altogether eliminated. This is supported by several studies (e.g., [70][71][72]), which found that alterations of ambient temperature tend to affect the timing and periodicity of sleep, while altering temperature far outside the thermal neutral zone can affect sleep duration as well. A study in bats found that when ambient temperatures exceeded 35 • C, no sleep was observed [73].…”
Section: Lights-offsupporting
confidence: 53%
“…Both animal and human studies have demonstrated disturbed sleep with thermal manipulations that activate heat or cold stress mechanisms (20,40). Thus, beyond the physiological range that we applied, a further increase in skin temperature is likely to disturb sleep-onset mechanisms rather than facilitate it at some point.…”
Section: Discussionmentioning
confidence: 94%
“…En los análisis post hoc, solamente la fase N3 tuvo diferencias significativas con las otras fases de sueño en ambos ciclos NMOR-MOR, lo que sugiere que esta fase contribuye con la diferenciación de la respuesta termorreguladora. Además, durante el sueño MOR la regulación de la temperatura está ausente, 22,24,25 con tal ausencia de los mecanismos reguladores de la temperatura los mamíferos se comportarían como animales poiquilotermos. 26 Sin embargo, los estudios que sustentan la falta de regulación de la temperatura en el sueño MOR se han realizado principalmente en mamíferos no humanos.…”
Section: Discussionunclassified